2016
DOI: 10.1186/s12888-016-0833-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk assessment in patients with a severe mental illness: a systematic review and meta-analysis

Abstract: BackgroundCardiovascular risk (CVR) has been observed to be higher in patients with severe mental illness (SMI) than in the general population. However, some studies suggest that CVR is not equally increased in different subgroups of SMI. The purposes of this review are to summarise CVR scores of SMI patients and to determine the differences in CVR between patients with different SMIs and between SMI patients and the control-population.MethodsMEDLINE (via PubMed) was searched for literature published through A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 64 publications
(76 reference statements)
0
26
0
Order By: Relevance
“…47 Our study found that 6.8% of women and 4.3% of men had a diagnosis of severe mental illness affects and it was associated with a 14% increased risk of cardiovascular disease for women and a 13% increased risk for men (model B). This is independent of the risk associated with atypical antipsychotics and hence both factors have been included separately as they will have a compound effect on cardiovascular risk.…”
Section: Severe Mental Illnessmentioning
confidence: 65%
“…47 Our study found that 6.8% of women and 4.3% of men had a diagnosis of severe mental illness affects and it was associated with a 14% increased risk of cardiovascular disease for women and a 13% increased risk for men (model B). This is independent of the risk associated with atypical antipsychotics and hence both factors have been included separately as they will have a compound effect on cardiovascular risk.…”
Section: Severe Mental Illnessmentioning
confidence: 65%
“…People with psychosis have increased risk of cardiovascular illness (Foguet-Boreu et al 2016) including in early phases of the illness (Correll et al 2014). But they are less likely than others to receive appropriate health care (Ayerbe et al 2018;De Hert et al 2011;Laursen et al 2014;Mitchell et al 2015).…”
Section: Monitoring Cardiovascular Risk Factors and Treatment Of Physmentioning
confidence: 99%
“…Physical disorders account for high morbidity, high mortality and earlier death for persons with psychosis, compared to the general population (Chang et al 2011;Heiberg et al 2018;Hjorthoj et al 2017;Kilbourne et al 2009;Lawrence et al 2013;Nordentoft et al 2013;Osby et al 2016;Saha et al 2007). A major part of this is due to cardiovascular and metabolic disorders including heart disease, hypertension, diabetes, hyperlipidemia and obesity (Correll et al 2014;Foguet-Boreu et al 2016;Stubbs et al 2015;Vancampfort et al 2016). Smoking, unhealthy diet, low physical activity and low medical and dental care contribute to physical illnesses and shorter lives (Correll et al 2017;Kisely et al 2015a, b;Vancampfort et al 2015;Wey et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Framingham risk scores (11) apply an algorithm that calculates the predicted CVD risk from risk factors such as diabetes, dyslipidemia, hypertension (23)(24)(25), smoking, and obesity (26,27). This risk calculator is frequently used in the general population but has also been applied to population groups with SMI (28). The prevalence of these risk factors is considerably raised in people with schizophrenia (4, 29-31) and people with schizophrenia have been shown to have higher risk scores than the general population (32)(33)(34).…”
Section: Framinghammentioning
confidence: 99%